2004
DOI: 10.4049/jimmunol.172.6.3758
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cationic Peptide LL-37 Induces Activation of the Extracellular Signal-Regulated Kinase and p38 Kinase Pathways in Primary Human Monocytes

Abstract: LL-37 is a cationic peptide that is found in the granules of neutrophils and is secreted by epithelial cells from a variety of tissues. Levels of LL-37 in vivo increase upon infection, and its production and secretion are increased upon stimulation with proinflammatory mediators. It has been postulated that LL-37 modulates the immune response by interacting with the effector cells of innate immunity; however, the mechanism of this interaction is unknown. LL-37 induced phosphorylation and activation of the mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
232
2
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(256 citation statements)
references
References 51 publications
19
232
2
3
Order By: Relevance
“…Similarly, FPRL-1 expression was not seen in cultured keratinocytes or in whole skin by immunostaining. This result agrees with recent studies demonstrating that FPRL-1 is not involved in LL-37-induced activation of epithelial cells (21) or monocytes (23).…”
Section: Cathelicidin Peptide-induced Il-8 Production In Keratinocytesupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, FPRL-1 expression was not seen in cultured keratinocytes or in whole skin by immunostaining. This result agrees with recent studies demonstrating that FPRL-1 is not involved in LL-37-induced activation of epithelial cells (21) or monocytes (23).…”
Section: Cathelicidin Peptide-induced Il-8 Production In Keratinocytesupporting
confidence: 83%
“…Previous investigations showed that cell activation and signaling by LL-37 can be G i protein dependent (19) or independent (23). Therefore, the IL-8 response was evaluated after treatment of keratinocytes with the G i inhibitor, pertussis toxin (PTX), in the presence or the absence of LL-37 or D-LL-37.…”
Section: Cathelicidin Peptide-induced Il-8 Production In Keratinocytementioning
confidence: 99%
“…Cathelicidin has been suggested to stimulate leukocyte recruitment and cytokine release in a receptor-specific manner (5,21,22). Thus, if a high-stringency receptor interaction was required to inhibit LPS activation of DC, structural modifications would be expected to eliminate this response.…”
Section: Cathelicidin Peptides Directly and Selectively Alter Receptomentioning
confidence: 99%
“…For example, human neutrophil peptides (HNPs; ␣-defensins) are chemotactic for resting, naïve CD4 T cells, CD8 T cells, and immature dendritic cells (DCs), whereas cathelicidins [LL-37 in the human; mouse cathelinrelated antimicrobial peptide (mCRAMP) in the mouse] are chemotactic for PMN, monocytes/macrophages, and T cells [10,11]. Cathelicidins also activate MAPK pathways in monocytes/macrophages, promoting the in vitro differentiation of precursor monocytes into DCs [12,13]. Finally, alarmins exhibit potent in vivo-immunoenhancing activity.…”
Section: Common Characteristics Of Alarminsmentioning
confidence: 99%